2022
DOI: 10.3389/fmolb.2022.909151
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride and Triglyceride-Rich Lipoproteins in Atherosclerosis

Abstract: Cardiovascular disease (CVD) is still the leading cause of death globally, and atherosclerosis is the main pathological basis of CVDs. Low-density lipoprotein cholesterol (LDL-C) is a strong causal factor of atherosclerosis. However, the first-line lipid-lowering drugs, statins, only reduce approximately 30% of the CVD risk. Of note, atherosclerotic CVD (ASCVD) cannot be eliminated in a great number of patients even their LDL-C levels meet the recommended clinical goals. Previously, whether the elevated plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 281 publications
0
40
0
Order By: Relevance
“…Furthermore, the elevated plasma levels of sdLDL are generally accompanied with reduced levels of HDL-C and Apo A-I, and elevated levels of TG and ApoB. It has been well-documented that HDL and Apo A-I are atheroprotective, while TG- and ApoB-containing lipoproteins are atherogenic ( Diffenderfer and Schaefer, 2014 ; Zhang et al, 2022 ).…”
Section: Atherogenic Mechanisms Of Ldlmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the elevated plasma levels of sdLDL are generally accompanied with reduced levels of HDL-C and Apo A-I, and elevated levels of TG and ApoB. It has been well-documented that HDL and Apo A-I are atheroprotective, while TG- and ApoB-containing lipoproteins are atherogenic ( Diffenderfer and Schaefer, 2014 ; Zhang et al, 2022 ).…”
Section: Atherogenic Mechanisms Of Ldlmentioning
confidence: 99%
“…However, PCSK9i show attractive lipid-lowering and anti-atherosclerotic effects in practice ( Cannon et al, 2015 ; Chaudhary et al, 2017 ; Guo et al, 2020 ). As we reviewed recently, angiopoietin-like protein (ANGPTL), such as ANGPTL3, plays a key in regulation of both cholesterol and TG via inhibition of LPL ( Zhang et al, 2022 ). The antisense oligonucleotide of ANGPTL3 has been applied to familial hypercholesterolemia and is now in phase 3 clinical trial ( Graham et al, 2017 ).…”
Section: Therapies Targeting Ldl-pmentioning
confidence: 99%
“…To investigate the underlying mechanisms, real-time quantitative polymerase chain reaction (RT-qPCR) and Western Blotting experiments were used for determining the expression of lipid metabolism-related genes and proteins, respectively. As accumulating evidence have demonstrated that gut microbiota may modulate obesity ( 10 , 23 ), the effect of fenofibrate on gut microbiota in ob/ob mice was also analyzed in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, TG accumulation in the liver is defined as fatty liver diseases including NALFD and non-alcoholic steatohepatitis, which currently have no approved drugs for therapy ( 8 , 9 ). Furthermore, TG is a residual risk factor of CVD ( 10 ). Theoretically, drugs with TG-lowering activity have a potential application for treatment of TG accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation